REPRESENTASI ASPEK MORAL DALAM KUMPULAN CERPEN OTOK KARYA W.N. RAHMAN (KAJIAN SOSIOLOGI SASTRA) - Senna Malinda, - (2022)
This study aims to describe the structure of the short story and describe the moral aspects represented in the collection of short stories Otok by W. N. Rahman. The material objects in this study are the short stories "Otok", "Sandal Kulit Bapk", and "Jalan" contained in the collection of short stories Otok by W. N. Rahman (2018). This study uses the structuralism approach proposed by Todorov, in this section the structure of the selected short stories will be analyzed which includes analysis of: (1) analysis of syntactic aspects, (2) analysis of semantic aspects, and (3) analysis of verbal aspects (pragmatics). ). Then, the sociological approach to literature will ultimately produce values and moral representations in the three short stories that have been selected. The data used in this study are in the form of words, phrases, sentences, and paragraphs contained in the three short stories selected from the collection of short stories Otok. The data collection technique in this research is library technique. The results showed the structure of the story in the short stories analyzed, including plotting and plot, characters and characterizations, setting, theme, type of storytelling, speeches that were present in the short story, and the point of view used in the story. The results of the sociological analysis describe how the moral aspects are represented in the three short stories. The moral aspects found in these three short stories are ultimately linked to the reality in society and strengthened by sources that exist in real life. After analysis, it can be seen that these three short stories contain moral values that the author tries to convey to his readers. These moral values are expected to build character and motivate readers to be able to do good in social life. So, it becomes a means to make yourself better.